Applying Nodal Governance to Combat Cybercrime: A Novel Approach (Journal of The Colloquium for Information Systems Security Education, 2017)
This paper will address the impact of the ever-increasing phenomenon of cybercrime in America. It will argue that cybercrime as a new genre of illegal behavior (criminality) is having a significantly negative impact on key aspects of America's national security, financial prosperity, and public safety. The premise of the paper is that the contemporary cyberthreat landscape is an evolving target surface with a growing cast of nation-states, transnational organized criminal organizations, and other criminal actors who are continually changing and updating their modus operandi to maintain an advantage over cybersecurity defenders. Moreover, as cybercrime incidents increase in frequency, harm, danger, and cost, the cybersecurity programs of public and private sector defenders may be incapable of effectively countering the threat, and the resulting growth in scale of cybercrime will continue to challenge and possibly overwhelm the capabilities of the federal-centric national cybersecurity strategy currently employed to counter this threat. The increasing and invasive nature of cybercrime mandates a critical and urgent need for enhanced capabilities and increased levels of expertise in combating, preventing, investigating, and policing cybercrime incidents. This paper recommends that American policymakers continue to recognize the level of threat presented by this damaging and noxious form of crime and in response adopt policies that foster implementation of an overarching national cybersecurity strategy based on the nodal governance of security. The paper recommendations that the U.S. government create operational policies and funding provisions to include and maximize the use of civil sector's capabilities and enhance law enforcement capabilities by expanding the use of local, state, and county police agencies in the campaign against cybercrime.
Keywords: cybercrime; cybersecurity; cyberthreat; nodal governance